Detection and molecular characterisation of Cryptosporidium spp. in Swedish pigs - Emelie Pettersson; Harri Ahola; Jenny Frössling; Per Wallgren; Karin Troell (Acta Veterinaria Scandinavica, 2020)
Abstract Background Cryptosporidium is a genus of apicomplexan parasites that cause enteric disease in vertebrates. In pigs, infections are most often asymptomatic, but may result in diarrhoea and poor growth. The most common species detected in pigs are C. suis and C. scrofarum with low zoonotic potential. C. parvum, with higher zoonotic potential, may also be found. As previous knowledge on the occurrence of Cryptosporidium in Swedish pigs is scarce, this was investigated in our study. Faecal samples from 13 pig herds were collected and a total of 222 pooled pen samples, from suckling piglets (n = 48), growers, aged 6–12 weeks (n = 57), fatteners, aged 13–24 weeks (n = 67) and adult animals (n = 50) were included. Samples were analysed using microscopy and positive samples were further analysed using polymerase chain reaction and sequencing of the 18S rRNA gene and the 28S rRNA gene to determine species. Results Cryptosporidium spp. were detected in all sampled herds and in 25% (56/222) of the individual pen samples. Infections were most common in growers and fatteners with 51% (29/57) and 35% (20/67) positive samples in each group, respectively. The piglets had 8% (4/48) positive samples and adults had 6% (3/50). Species determination showed C. suis and C. scrofarum in piglets and growers, C. scrofarum in the fatteners, and C. suis and C. parvum in the adults. Although no mixed infections could be confirmed we saw signs of double peaks in the 28S rRNA gene chromatograms, possibly indicating more than one species present per sample. Conclusion Cryptosporidium spp. were detected on every sampled farm and in 25% of the individual pen samples in our study. We therefore conclude that Cryptosporidium spp. are present and likely common in Swedish pig herds, where pigs are loose and reared on solid floors. However, none of the farms reported any problems with poor weight gain, diarrhoea, or reduced appetite in their pig herds. The pig adapted C. suis and C. scrofarum were the predominant species identified. Two samples were positive for the more zoonotic C. parvum, and pigs should hence not be disregarded as a possible source of zoonotic cryptosporidiosis.